2011
DOI: 10.3109/0142159x.2011.610838
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians prefer simple educational tools for implementing practice change

Abstract: Background: Successful implementation of practice change requires educational tools that engage and motivate clinicians. Aim: To examine clinician usage and preference for different educational tools when a multifaceted strategy was used for implementation of new recommendations for managing newborns at risk of sepsis. Methods: Seminars, web-based tutorial, handouts, pocket cards and web-based management algorithm were used to educate health professionals. Ninety-two clinicians attended seminars and completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…1). Interestingly, in the study performed by Jeffries & Vibhuti (2011), it was noted that, when provided with different educational tools, clinicians prefer to learn from pocket cards and seminars (i.e. tools that are simple and readily accessible).…”
Section: Discussionmentioning
confidence: 99%
“…1). Interestingly, in the study performed by Jeffries & Vibhuti (2011), it was noted that, when provided with different educational tools, clinicians prefer to learn from pocket cards and seminars (i.e. tools that are simple and readily accessible).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that pocket cards are a preferred educational tool even when other options for learning are available. 22 The clinical utilization of any pocket card is related to the context and the user's perception of clinical relevance, which itself has many mitigating factors. It can be speculated that pocket cards may be more valuable for novice practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…One previous study showed that web-based resources were self-reported to be used less than a pocket card resource but qualify that the web-based resource required log in and several steps to access as a possible explanation. 22 The PDF electronic version in this study could be saved easily on any portable device and later accessed with a few clicks. Most participants expressed a preference for the laminated hard copy, although some did prefer to have both available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Online resources should be judiciously utilized for training and public awareness. [23] Industry partnership should be sought for education and research. Industry is seen shying away from clinical research in sepsis for various reasons.…”
Section: Sepsis Clockmentioning
confidence: 99%